Biomass Production and Carbon Sequestration in Different Agroforestry Systems in Tarai Region of Central Himalaya - Yadava, Anil Kumar (Indian Forester, 2010)
The present investigation deals with effect of structural composition of agroforestry system, number of woody perennial involved in the system and the management practices plays a major role in influencing the biomass level, carbon storage, C02 mitigation potential and total carbon sequestration (in trees) of 70.59 tha-1,21.38 tha-1,116.29 tha-1 and 18.53 t C ha-1 in system S, followed by 68.53 tha-1, 20.63 tha-1,113.03 tha-1 and 17.601 C ha-1 in system S4, respectively. It was also observed that all the agroforestry systems can sequester more carbon as compared to sole agricultural land use systems. It was also observed that Populus deltoides + wheat and Populus deltoides + lemon grass under block plantation have the maximum potential to sequester carbon than the boundary plantations of Populus deltoides and Eucalyptus hybrid.